ThaSala Street Art: Restoring the Colors to the City in the Time of Pandemic - Vorachart, Varunyu; Hosap, Witthaya; Preeyawongsakul, Patibut (Street Art & Urban Creativity, 2021)
Thailand’s street art circle is now gaining popularity. As a tourism country, Thailand has a policy to promote tourism in a number of ways. Therefore, street art has been used to promote tourism a variety of locations. In the midst of the COVID-19 crisis, this article reveals a story of a street art initiative in an overlooked district in southern Thailand to establish a new tourist attraction. The article covers the story since the beginning of the idea, specifies concepts and processes behind the showcase, interviews various stakeholders for insights and provides additional thoughts on street art creation. It also summarizes the lessons learned from the project that has been done through interviews with stakeholders from different perspectives to use as a guideline for further street art project development.